The issue of nation-building in independent Kazakhstan in the works of domestic scientists: a political analysis (Journal of Philosophy Culture and Political Science, 2024)
in this paper Kazakh researches literature review conducted on the topic of nation building in Kazakhstan. Based on articles, books and monographs published in «Bulletin of the L.N. Gumilyov Eurasian National University», «Journal of Philosophy, Culture and Political Science» of the al-Farabi Kazakh National University, «Kazakhstan-Spectr» of the Kazakhstan Institute for Strategic Studies under the President of the Republic of Kazakhstan, and e-library of the L.N. Gumilyov Eurasian National University. The purpose of the article is to identify issues of nation-building that have not been considered by Kazakh scientists. The results of the article will serve as the basis for further and in-depth study of aspects of nation building in Kazakhstan.This article provides an overview of studies of kazakh scientists dedicated to issues of nation-building in the period after the country gained independence. The work highlights the diversity of aspects associated with the formation of national identity, including both the state-forming ethnic group (Kazakhs) and other ethnic groups living in Kazakhstan. The focus of research in the early 90s was the formation of nations around national identity.In the following years scientists paid attention to the strategies of nation building - civil or ethnic, as well as the influence of the Internet, globalization and ideology through the education system. Noted that different researchers have identified different aspects, such as strengthening the Kazakh language and economic development as key elements of nation-building.           However, in the reviewed works not all aspects supported by empirical data, and the vastness of the topic makes it difficult to formulate specific conclusions. Some studies rely on regulations and government programs that, which creates difficulties in assessing the nation-building process.  In conclusion, it is emphasized that in the 90s a new stage of research into nation-building began in post-Soviet countries, including Kazakhstan. Despite the extensive study of certain aspects, questions remain unresolved about the formation of a nation, the role of the state language, the interest of other ethnic groups in the language, the impact of the education system and the development of the film industry on national identity.        Keywords: memory, historical memory, cultural memory, memory research, memory trauma, nation-building, national identity, national idea, national code, national spirit, national/Kazakh culture, national traditions and customs